Iluminasi Manuskrip Jawa sebagai Inspirasi Desain Undangan Pernikahan - Ekowati, Venny Indria; Aryulita, Erlin; Dwiadmojo, Ghis Nggar; Hadirman, Hadirman (Lembaga Yasin AlSys, 2025)
Conserved Javanese manuscripts hold a wealth of visual richness and aesthetic value that remains largely unexplored, particularly in the illuminative elements which serve not only as decoration but also as illustrative support to the textual content. This study aims to propose an invitation card design inspired by the illuminations found in ancient manuscripts, as a form of cultural adaptation within the creative industry. The research employs a descriptive-qualitative method and content analysis. The primary object of study is the illumination in the manuscript Serat Jayalengkara Wulang, codex Add MS 12310, housed in the British Library. The adaptation process comprises five stages: (1) selection of illumination elements, (2) redrawing using the Procreate application, (3) stylization for form simplification, (4) layout arrangement for the invitation design, and (5) final rendering for production purposes. The end product is a market-ready digital invitation design, available for e-commerce distribution. This study demonstrates that Javanese manuscript illuminations can be creatively adapted as visual elements that hold both aesthetic and historical value, while also enhancing product appeal within the creative industry. The findings open new possibilities for utilizing intangible cultural heritage, which has traditionally focused more on script than on visual elements such as illumination.